Administration Procedure for Selling Bear Brand Milk Using ND6 On PT. Aneka Rasa Citra Sejati, Jakarta - Rajagukguk, Peter; Hardani, Hardani; Fadholi, Arief; Haryono, Bambang (International Journal of Social and Management Studies, 2022)
This study aims to analyze the implementation of the sale of Bear Brand Milk during the covid-19 pandemic at PT. Various Taste of True Image, Jakarta. Companies engaged in the distribution of products PT. Nestle Indonesia in the form of coffee, cereals, and several kinds of milk, one of which is bear milk. The target market is Traditional Markets, Bakery, Hotels, Restaurants, Cafés, Business Industries, School Canteens, Mini Markets, and Cooperatives. The implementation of sales is an important stage that has been determined by the company in the context of the company's operational activities. In conducting sales input using the ND6 program. This type of research is policy research (policy research) with a qualitative descriptive method. Methods of data collection using, observation, interviews and documentation. Data analysis phase with preparation, exploration, and reporting. This study shows that the implementation of sales starts from consumer orders to sales, is forwarded to the administration to make sales invoices and letters of delivery of goods. The invoice is checked by the head of the warehouse, and loading is carried out. When it is finished loading, the invoice and travel document are handed over to the driver and then sent to the customer's address, the consumer receives the goods and signs the delivery letter. Document data required in the form of direct order (Additional Order) or CMO (Cofirm Monthly Order) order a month earlier for products that are out of stock, PO (Purchase Order) Sales Invoice, and Travel Letter.